Caracterização molecular e fenotípica de Staphylococcus coagulase negativos isolados de mastite bovina - Custódio, Dircéia Aparecida da Costa (2019)
Coagulase-negative Sthapylococci (CNS) is a heterogeneous bacterial group that has high importance in bovine mastitis etiology, especially in herds in which the Staphylococcus aureus and Streptococcus agalactiae infections were controlled. The accurate identification and the characterization of these pathogens are extremely relevant because of its high importance in Brazilian herds.,. At that, the present study aimed: 1) to identify the CNS isolates using the Matrix Associated Laser Desorption-Ionization - Time of Flight (MALDI-TOF); 2) to verify the presence of enterotoxins genes (sea, seb, sec, sede see), alfa and beta hemolysin genes (hla e hlb) and biofilm gene (icaAD); 3) to evaluate phenotypically the alfa and beta hemolisins and biofilm productions, and 4) to evaluate the antimicrobial and antisseptic susceptibility profiles of strains. For these purposes, were used 123 CNS strains isolated from milk of cows with mastitis, from Minas Gerais south region. The DNA extraction was performed by guanidine method. Multiplex PCR was used to verify the presence of genes related to hemolysin and enterotoxins expression, and single plex PCR to IcaAD gene. In vitro biofilm production was evaluate by culture of strains in Red Congo agar and the hemolysin production by culture in 5% sheep blood agar. The antimicrobial and antisseptic tests were performed using the minimum inhibitory concentration (MIC) technique according to CLSI (2018). Eight species of CNS were identified by MALDI-TOF. The most frequent specie was Staphylococcus chromogenes (71.55%), following by S. hyicus (7.32%), S. aureus (4.88%), S. epidermidis (4.88%), S. haemolyticus (4.06%), S. warneri (3.25%), S. simulans (3.25%) e S. saprophyticu s (0.81%). The molecular tests showed that all isolates were negative to enterotoxins genes and that 7.31% were positive to icaAD gene. PCR tests showed that 78.86% of the isolates were negative to hemolysin genes hla and hlb and 4.88% was positive to both genes; 16.26% were positive only to hla and none isolate was positive only to hlb. In vitro phenotypic tests to biofilm and hemolysin productions showed that 84.55% of the isolates were positive to biofilm and that 78.86% of strains did not showed hemolytic activity. The antisseptic susceptibility tests demonstrated 100% of susceptibility to all antiseptics, except glutaraldehyde, in which 80.49% of the isolates were resistant in concentration of 2%. Antimicrobial susceptibility tests results showed 44 resistance profiles and the multidrug resistance phenomenon was observed in expressive proportion of the population studied. This study presents important contributions about epidemiology, virulence, and resistance profiles of CNS associated with bovine mastiti s in Brazilian herds.